PRODUKTIVITAS KERJA PEGAWAI PEMERINTAH DESA DI KABUPATEN BARRU - Mailand, Arisman; Malik, Ihyani; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to determine the work productivity of employees at the Tellumpanua Village office, Tanete Rilau District, Barru Regency. The research method used is descriptive qualitative with data collection techniques through interview observation. The results of the research show that work productivity at the Tellumpanua village office, Tanete Rilau District, Barru Regency, by looking at three indicators, namely quantity, quality of work and punctuality, is quite good. The quantity of employee work based on interview results shows that employees are able to complete their tasks well within a certain amount. Then in terms of quality, according to the results of the interview, it was stated that the staff had tried to carry out their duties and responsibilities based on the leadership's direction and guidance in accordance with the operational standards set by the government. This is an indicator of punctuality, Tellumpanua village office employees have tried to complete tasks according to the applicant's request. However, employees' timeliness indicators still need special attention regarding their discipline